Pengembangan Sistem Informasi Akademik Terintegrasi Berbasis Web Mobile Pada Lembaga Pendidikan Menengah Atas - Sandy Maulana Rifqi; Ledy Elsera Astrianty (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Academic information dissemination at Senior High School has been carried out conventionally, often resulting in delays in providing attendance, class schedules, and grade reports to students and parents. The limitation of non-real-time information access impacts the lack of parental supervision regarding student discipline and academic progress. This research aims to design and build a web and mobile-based Academic Information System capable of integrating school data management digitally, quickly, and accurately. The system development method used is the Waterfall method, including requirement analysis, system design, implementation, testing, and maintenance. The system was developed using the Laravel framework for the web-based admin dashboard and the Flutter framework for the mobile application for students and parents, supported by a MySql database. This research provides a scientific contribution in the form of a cross-platform integration architecture (dual-framework) connected via RESTful API to overcome data communication asymmetry in educational institutions. This cross-platform integration is implemented to facilitate administrators' needs in large master data management while providing enhanced accessibility for mobile users. Functional testing using the Black Box Testing method showed that all main features operate as expected, and User Acceptance Testing (UAT) resulted in an average score of 86.0%, falling into the